Exceptionally long CDR3H of bovine scFv antigenized with BoHV-1 B-epitope generates specific immune response against the targeted epitope. (September 2016) - Pasman, Yfke; Soliman, Caroline; Ramsland, Paul A.; Kaushik, Azad K.
Highlights: Identification of a configurational B cell epitope on gC enevelope protein of bovine herpes virus-1. Antigenization of bovine scFv by B-epitope grafting into the exceptionally long CDR3H (61 amino acids). B-epitope grafted into the CDR3H of scFv retains its native configuration. Antigenized scFv induces robust and specific immune response in natural host. Abstract: We discovered that some bovine antibodies are amongst the largest known to exist due to the presence of an exceptionally long CDR3H (≥49 amino acids) with multiple cysteines that provide a unique knob and stalk structure to the antigen binding site. The large CDR3H size, unlike mouse and human, provides a suitable platform for antigenization with large configurational B-epitopes. Here we report the identification of a B-epitope on the gC envelope protein of bovine herpes virus type-1 (BoHV-1) recognized by a bovine IgG1 antibody. The identified 156 amino acid long gC fragment (gC156) was expressed as a recombinant protein. Subsequently, a functional scFv fragment with a 61 amino-acid long CDR3H (scFv1H12) was expressed such that gC156 was grafted into the CDR3H, replacing the "knob" region (gC156scFv1H12 or Ag-scFv). Importantly, the Ag-scFv could be recognized by a neutralizing antibody fragment (scFv3-18L), which suggests that the engraftment of gC156 into the CDR3H of 1H12 maintained the native conformation of the BoHV-1 B-epitope. A 3D model of gC156 was generated using fold-recognition approaches and this was grafted onto the CDR3H stalk of the 1H12 Fab crystal structure to predict the 3D structure of the Ag-scFv. The grafted antigen in Ag-scFv is predicted to have a compact conformation with the ability to protrude into the solvent. Upon immunization of bovine calves, the antigenized scFv (gC156scFv1H12) induced a higher antibody response as compared to free recombinant gC156. These observations suggest that antigenization of bovine scFv with an exceptionally long CDR3H provides a novel approach to developing the next generation of vaccines against infectious agents that require induction of protective humoral immunity.